Influence of Application of Learning Strategies Against Super Item Mathematical Reasoning Ability of Junior High School Students - Darto, Delva Nora (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The problem in this research is the lack of mathematical reasoning skills of students of MTs Darul Hikmah Pekanbaru. This study aims to determine the effect of the application of Super Item learning strategies on mathematical reasoning skills in the context of teaching students of MTs Darul Hikmah Pekanbaru. This research is a Quasi Experiment with Posttest Only Design Group design. The population in this study is students of MTs Darul Hikmah Pekanbaru : 134 students consisting of four classes. Students of class VIII.B2 MTs Darul Hikmah Pekanbaru were taken as the samples in the experimental class and students of VIII.B5 were selected as the samples in control class. The findings show that result obtained were that value tcalculated = 3,45, with a significant level of 5% and dk = 65 from the distribution list obtained ttabel = 2. Therefore the value tcalculated > ttabel because 3,45 > 2, So that Ha accepted and Ho rejected. This means that there are influences of mathematical reasoning skills for the students who were taught using of learning strategies Super Item. It can be concluded that the application of Super Item learning srategiesdid have some influences onstudentsâ mathematical reasoning skills in MTs Darul Hikmah Pekanbaru.